Design low-voltage low-power current reference in 180nm - Diseño de un espejo de corriente a baja potencia y voltaje en 180nm - Diego Fernando Jaramillo Calderon (ACI Avances en Ciencias e Ingenierías, 2020)
This paper describes design improvement of a current reference, originally based on dual-threshold voltage current mirror stages, these stages have been modified in order to improve the temperature dependence of the current of a diode-connected transistor and the figures of merit to compare this circuit both the base-circuit. The proposed solution has been designed in a 0.18 \text{\ensuremath{μ}m} technology and analyzed through circuit simulation. Simulation results, when a body-bias generator is used, show an output current of 342 nA and a power consumption below 513 nW at the maximum operating voltage of 1.5 V and at the room temperature. The line sensitivity is 1 %/V, while the temperature coefficient is 17 ppm/°C. On the other hand, when the body-bias generator is neglected, the circuit shows an output current of 188 nA and a power consumption below 282 nW at the maximum operating voltage of 1.5V and at the room temperature. The line sensitivity is 2.89 %/V, while the temperature coefficient is 23 ppm/°C.